Increase in calcidiol level is associated with improved sternal bone healing after cardiac surgery with sternotomy-REINFORCE-D trial results - Černý, Dalibor; Čečrle, Michal; Sedláčková, Eva; Míková, Barbora; Drncová, Eva; Skalský, Ivo; Mieresová, Marie; Halačová, Milada (Trials, 2025)
INTRODUCTION: Heart surgery is associated with a sternotomy in most patients. Low serum calcidiol level below 80 nmol/l carries the risk of bone loss as a risk factor in sternotomy healing. OBJECTIVES: The primary objective was to compare postoperative complications of sternotomy healing in two groups of patients treated with cholecalciferol or placebo. Secondary objectives were focused on the degree of sternal healing, length of hospitalization, number of days spent in ICU and mechanical ventilation, and number of repeated hospitalizations for sternotomy complications. METHODOLOGY: Monocentric, randomized, double-blind, placebo-controlled, prospective study was conducted from September 2016 to December 2020 at Na Homolce Hospital. Of the 216 originally recruited and randomized subjects, 141 completed the study. Seventy-two subjects were enrolled in the cholecalciferol arm, and sixty-nine subjects in the placebo arm. The detailed methodology has been published previously. The results are presented as a comparison between two groups: calcidiol above 80 nmol/l (saturated subjects) and the calcidiol lower or equal to 80 nmol/l (unsaturated subjects). RESULTS: Statistics include 141 subjects. After a 6-month follow-up, CT imaging and calcidiol levels were performed. PRIMARY OBJECTIVE: postoperative complications in sternotomy were not among the population under or above 80 nmol/l statistical difference (p = 0.907). SECONDARY OBJECTIVES: monitored parameters did not differ between individual arms. But the key was the state of saturation with calcidiol (> 80 nmol/l), which was associated with a significantly lower risk of complete non-healed sternotomy (p = 0.008). CONCLUSION: Optimal calcidiol level (> 80 nmol/l) indicates a positive trend towards greater sternal healing. Cholecalciferol oral administration can be considered as a safe method how to achieve the required calcidiol concentration. TRIAL REGISTRATION: EU Clinical Trials Register, EUDRA CT No: 2016-002606-39.
Keywords: Female; Cardiac Surgical Procedures; Calcifediol; výsledek terapie; ženské pohlaví; Cardiac surgery; Wound Healing; kalcifediol; sternotomie; Time Factors; časové faktory; lidé; dvojitá slepá metoda; kardiochirurgické výkony; pooperační komplikace; Treatment Outcome; sternum; Bone healing; Vitamin D; prospektivní studie; Double-Blind Method; Male; Postoperative Complications; cholekalciferol; Prospective Studies; Aged; Cholecalciferol; Calcidiol serum concentration; Sternum; hojení ran; lidé středního věku; senioři; mužské pohlaví; Sternotomy; Middle Aged; Humans